Dithiocarbonate and trithiocarbonate interactions with pyrite and copper - Vermaak, M.K.G. (Matthys Karel Gerhardus) (University of Pretoria, 2013)
Dissertation (MSc (Metallurgy))--University of Pretoria, 2008.